2007
DOI: 10.1124/dmd.107.019265
|View full text |Cite
|
Sign up to set email alerts
|

CYP2C19 Inhibition: The Impact of Substrate Probe Selection on in Vitro Inhibition Profiles

Abstract: ABSTRACT:Understanding the potential for cytochrome P450 (P450)-mediated drug-drug interactions is a critical part of the drug discovery process. Factors such as nonspecific binding, atypical kinetics, poor effector solubility, and varying ratios of accessory proteins may alter the kinetic behavior of an enzyme and subsequently confound the extrapolation of in vitro data to the human situation. The architecture of the P450 active site and the presence of multiple binding regions within the active site may also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
37
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 28 publications
4
37
0
Order By: Relevance
“…The selection of appropriate CYP3A4 probe substrates for in vitro studies has led to substantial debate. CYP2C9 (Kumar et al, 2006), CYP2C19 (Foti and Wahlstrom, 2008), and CYP3A4 (Kenworthy et al, 1999; Stresser et al, 2000) have exhibited probe substrate-dependent inhibition for in vitro studies. The correlation analysis of CYP3A4 DDI data from in vitro experiments has suggested that at least three probe substrate classes may exist for CYP3A4: benzodiazepine-like, dihydropyridine-like, and testosterone-like, possibly due to the presence of multiple binding regions within the CYP3A4 active site (Kenworthy et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The selection of appropriate CYP3A4 probe substrates for in vitro studies has led to substantial debate. CYP2C9 (Kumar et al, 2006), CYP2C19 (Foti and Wahlstrom, 2008), and CYP3A4 (Kenworthy et al, 1999; Stresser et al, 2000) have exhibited probe substrate-dependent inhibition for in vitro studies. The correlation analysis of CYP3A4 DDI data from in vitro experiments has suggested that at least three probe substrate classes may exist for CYP3A4: benzodiazepine-like, dihydropyridine-like, and testosterone-like, possibly due to the presence of multiple binding regions within the CYP3A4 active site (Kenworthy et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Accepted major +ve Perpetrators of CYP-mediated pharmacokinetic drug-drug interactions sensitivities of in vivo probes for drug metabolizing CYP enzymes other than CYP3A still require formal evaluation, particularly for CYP2C9 and CYP2C19, which together with CYP3A exhibit substrate-dependent inhibition in vitro [24,25]. The use of objective criteria facilitates appropriate re-classification when new information emerges.…”
Section: Cyp Inhibitorsmentioning
confidence: 99%
“…Fluoxetine also undergoes CYP2C19-mediated O-dealkylation to the p-trifluoromethylphenol metabolite (Liu et al, 2002). In addition, racemic fluoxetine and/or its enantiomers have been shown to be reversible inhibitors of CYP2D6 (Brosen and Skjelbo, 1991;Stevens and Wrighton, 1993), CYP2C19 (Kobayashi et al, 1995;Foti and Wahlstrom, 2008), CYP3A4 (von Moltke et al, 1994;Ring et al, 1995), and CYP2C9 (Schmider et al, 1997;Hemeryck et al, 1999). Fewer studies have been conducted examining the potential for fluoxetine to be a mechanism-based inhibitor of P450.…”
mentioning
confidence: 99%